The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/fsn3.685
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transportation, storage, and retail shelf conditions on lettuce quality and phytonutrients losses in the supply chain

Abstract: This study was initiated to investigate the impact of transportation, storage, and retail shelf conditions on lettuce quality and phytonutrients losses in the urban fresh produce market supply chain. Reducing postharvest losses is a priority to reduce the loss of the dietary‐based phytonutrients and to improve the health of the consumers. Limited information is available in South Africa related to the postharvest and nutrition loss in the urban fresh produce market supply chain. In this study, we quantified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 37 publications
1
7
0
1
Order By: Relevance
“…Lettuce stored at higher temperatures resulted in greater weight loss. However, moderate weight loss was observed for all storage temperatures compared to Managa et al [49], who reported 45.31% weight loss in Iceberg lettuce stored for 3 days at room temperature. According to Manolopoulou et al [50], this may be due to the high relative humidity generated around the head of lettuce when they are bagged.…”
Section: Discussionmentioning
confidence: 51%
“…Lettuce stored at higher temperatures resulted in greater weight loss. However, moderate weight loss was observed for all storage temperatures compared to Managa et al [49], who reported 45.31% weight loss in Iceberg lettuce stored for 3 days at room temperature. According to Manolopoulou et al [50], this may be due to the high relative humidity generated around the head of lettuce when they are bagged.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, it was confirmed that CAPE develops cytotoxic effects in concentrations ≥10 µM [14,15,16]. For the investigation of the anti-inflammatory effects of CA, CQA, and C-IA, a concentration of 10 µM was found to be ideal, since these concentrations are physiologically relevant as they are reachable by a 200 g serving of either crisp head lettuce or amaranth [4,9]. Furthermore, CA and C-IA showed recovery rates of 100% and 75% after 4 h incubation, which indicates a decent stability for further experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorogenic acid (3-caffeoylquinic acid, CQA), a related compound that is not found in amaranth leaves, but is widely distributed in other plants, also contains caffeic acid (CA) as a phenolic moiety. CQA has been shown to possess numerous biological properties, including antioxidant, anti-inflammatory, and anti-carcinogenic activities [5,6,7,8,9]. Previous studies showed that the biotransformation of CQA and C-IA by the gut microbiome is comparable and that both compounds can be partially resorbed by the human organism [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, in real supply chain conditions, factors other than temperature and relative humidity, such as mechanical injuries, microbial contamination, can also negatively affect the quality of the fresh produces which can cause an increase in product losses. Only in a few studies, the postharvest losses were quantified in real supply chain conditions in which the main objective was to quantify the postharvest losses for a specific commodity and country (Gogo et al, 2017;Managa et al, 2018;Rediers et al, 2009). However, to the best of our knowledge, no study has been carried out yet which aimed at comparing the postharvest losses in supply chains with good and poor handling practices.…”
Section: Introductionmentioning
confidence: 99%